IDENTIFIKASI INDEKS KINERJA BANGUNAN PEMECAH GELOMBANG PULAU BENGKALIS - Muhamad Ghifar Alharis; Manyuk Fauzi; Imam Suprayogi (Racic : Rab Construction Research, 2025)
To ensure their structural integrity and functional viability, it is essential to conduct condition assessments and evaluate performance indices. These serve as the foundation for operational and maintenance activities carried out by the responsible authorities This research aims to assess the condition and performance index of the breakwater structure in accordance with the standards set out in the aforementioned circular. The methodology adopted in this study is based on the guidelines within that document. Based on the analysis of the condition and performance indices of the Bengkalis Island breakwater, the coastal protection structures are generally in good condition, with performance index values ranging from 1.05 to 1.47. The recommended action for the coastal protection structures in Bengkalis Island is continued monitoring.